The Upper Proterozoic Redstone Copper Belt, Mackenzie Mountains, Nwt - Jefferson, Charles Wilson (Scholarship@Western, 1983)
The Redstone Copper Belt is a 300 km arcuate zone of late Proterozoic stratabound copper occurrences within the Coates Lake Group (proposed) in the Mackenzie Mountains, N.W.T., Canada. The Coates Lake Group was deposited on the eroded surface of shallow marine carbonates and tholeiitic basalts at the top of the Little Dal Group. Six main areas of deposition and preservation were controlled by growth faults during the early part of the Hayhook extensional tectonism (About 750 Ma).;Three formations within the Coates Lake Group record transgression from alluvial fan to sabkha and shallow platformal marine conditions (Thundercloud Formation, proposed); regression from restricted marine, lagoonal or lacustrine evaporite accumulation to alluvial carbonate sedimentation (Redstone River Formation); a transgression to low energy sabkha conditions (Transition Zone); then submergence to carbonate turbidite and mass-flow deposition below wave base (Coppercap Formation). Most of the lastic material was locally derived from underlying platformal carbonates of the Little Dal Group.;Stratabound occurrences of disseminated copper sulphide minerals are mainly in the Transition Zone between the Redstone River and Coppercap Formation. Sabkha conditions during copper deposition are shown by evaporites, cryptalgal laminites, red beds, ripple marks and desiccation cracks. Syngenetic to late diagenetic ages of mineralization are documented by step-wise upward-decreasing copper:iron ratios, stratigraphy, and association of copper sulphide minerals with sedimentary pores and diagenetic replacement textures. Active faults and coastal morphology appear to have controlled mineralization in a different way in each depositional embayment.;Anomalously abundant copper at the start of the Hayhook Orogeny could have been caused by any or all of the following: rifting with concommitant exhalative activity; leaching of underlying formations; and/or compactional dewatering of underlying formations. A limited number of chemical analyses suggest ...